On Pata–Suzuki-Type Contractions - Erdal Karapınar (Mathematics, 2020)
In this manuscript, we introduce two notions, Pata−Suzuki <semantics> Z </semantics> -contraction and Pata <semantics> Z </semantics> -contraction for the pair of self-mapping <semantics> g , f </semantics> in the context of metric spaces. For such types of contractions, both the existence and uniqueness of a common fixed point are examined. We provide examples to illustrate the validity of the given results. Further, we consider ordinary differential equations to apply our obtained results.